COMMUNITY STRUCTURE AND HEALTHINESS OF MANGROVE IN MIDDLEBURG-MIOSSU ISLAND, WEST PAPUA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Mangrove ecosystem plays important role in a small island’s existence and provided ecosystem services. Its functionality highly depends on the size, community structure, and ecosystem quality. A field study on the mangrove quality in a small island was conducted on Middleburg-Miossu Island as a series of Nusa Manggala Expedition 2018. The study was aimed to analyze the community structure and mangrove health index (MHI) of mangroves on the island related to remote sensing-based vegetation indices. Mangrove area was divided into four zones (Z1-Z4). The study results showed that the outmost zone was dominated by Sonneratia alba (IVI 263.32%), less than 50% of canopy coverage, more than 20 cm of diameter, and a lower height. Meanwhile, the other three landward zones were dominated by type C. tagal with more than 80% of canopy coverage and higher sapling density. Based on the MHI value, mangrove in Middleburg-Miossu island was categorized into moderate ranging from 38.7 to 60.7%. Based on AIC analysis, a combination of NBR, GCI, SIPI, and ARVI vegetation indexes showed the highest regression coefficient, R2-adjusted, for predicting MHI, which was 0.831. Interpolation of the predicted MHI value from the best model showed that 6.56 ha mangroves at the research site or 40.74% were in the healthy condition.